Correlation of gate leakage and local strain distribution in GaN/AlGaN HEMT structures. (September 2016) - Broas, M.; Graff, A.; Simon-Najasek, M.; Poppitz, D.; Altmann, F.; Jung, H.; Blanck, H.
Abstract: GaN/AlGaN HEMT structures are observed to undergo a reversible, drastic change in the leakage current when covered with an additional polymer passivation layer. The polymer layer induces a stress on the HEMT structures, which initiates material migration processes and the formation of structural defects, influencing the electrical performance. Local strain measurements were performed in the semiconductor, at the critical HEMT gate electrode, to evaluate the impact of the stress on the Schottky gates. The strain distributions in the structures were measured with nanobeam electron diffraction from electron-transparent samples at cross sections and longitudinal sections at the positions of high leakage currents. A variation of the strain distribution underneath the gate electrode was detected in a cross-sectional sample. On the contrary, only minor differences in the strain values were measured in the longitudinal sections at different photoemission sites. Finally, localized metal interdiffusion was detected at the sites with the highest photoemission intensities. Highlights: Leaky HEMT gate areas are analyzed with local strain and elemental mapping. Interdiffusion of Schottky contact metallization is found at the leaky locations. Strain maps display greater variation in the leaky locations compared to the non-leaky locations.